TRIPLE EXPONENTIAL SMOOTHING: FORECASTING PERBANDINGAN PENUMPANG KERETA API DAN PESAWAT TERBANG - Khoirin Azaro; Nur Indah Riwajanti; Anik Kusmintarti (Media Mahardhika, 2020)
This research aims to predict the number of train and airplane passengers in 2020. Forecasting of train and airplane passengers is interest to analyze and estimate consumer demand to help the train or airline company prepare effective and efficient planning. This type of research is descriptive quantitative and uses data taken from the Indonesian Statistic Agency (BPS). Data were analyzed using Exponential smoothing Method. Train and airplane passenger data shows trend and seasonal patterns so that the exponential method used is Triple Exponential smoothing. The results of the study show that train passengers in 2020 are increase. While forecast results related to aircraft passengers in 2020 also tend to increase.